The Correlation of Narcissism and Hubristic Motivation of Student Personality - Fomenko, Karyna (Psychological Prospects Journal, 2014)
In the article we examine terms hubristic motivation, striving for perfection, striving for superiority, narcissism, also views of foreign and native scientists to this problem. Research methods and of hubristic motivation and narcissism are given. Results of investigation of correlation between hubristic motivation and narcissism are shown. In the student’s age the traits of narcissistic personality are manifested in such settings as «Expectations of special treatment» and «Manipulation in interpersonal relationships». So the student is characterized by confidence in the fact that for them to be particularly relevant side environment irritation when their expectations about particular attitudes environment is not implemented. Students are more likely to use other people to enhance their own social position goals. Hubristic and narcissistic individual student disclosed in pursuit of advantages associated with narcissistic traits such as «The need for constant attention and admiration», «Immersion in fantasy», «Grandiose sense of self importance», «Deep feeling of envy», «Manipulation in interpersonal relationships». Students will express striving for perfection is also characterized by a narcissistic trait such as «The need for constant attention and admiration».